Why internal conflict deteriorates state capacity? Evidence from Colombian municipalities (2013)
Previous work has documented a negative correlation between internal conflict and state capacity. We attempt to shed light on mechanisms that underlie this relationship, using data for Colombian municipalities. We rely on identifying heterogeneous effects of different types of violent events on state capacity, taking advantage of variability across municipalities in the prevalence of specific manifestations of conflict and their intensity. Our findings suggest that events making civilians feel targeted affect the state's capacity to collect taxes, while those reflecting a stronger military capacity of illegal armies, in particular their large-scale attacks, affect the state's capacity to provide public goods.